Quantitative evaluation of retinal microvascular circulation in patients with obstructive sleep apnea–hypopnea using optical coherence tomography angiography - Cai, Yi; Sun, Guo-Sheng; Zhao, Long; Han, Fang; Zhao, Ming-Wei; Shi, Xuan (International ophthalmology, 2020)
Purpose To compare capillaries perfusion in macular areas at different layers and peripapillary region in radial peripapillary capillaries (RPC) between healthy subjects and subjects with obstructive sleep apnea–hypopnea (OSA) using spectral-domain optical coherence tomography angiography (OCTA). Methods Totally 16 eyes with mild-to-moderate OSA, 14 eyes with severe OSA and 22 control eyes were enrolled in this study. Every subject filled out the Berlin questionnaire and received a comprehensive ocular and physical examination. The clinical characteristics were collected, OCT and OCTA scans using OCTA RT XR Avanti (AngioVue software, Optovue Inc., Fremont, CA, USA) were performed and analyzed. Results Compared to the control group, the severe group had significantly higher VD in parafovea and perifoveal regions ( p = 0.031; p = 0.029) at the level of deep capillary plexus (DCP), whereas the mild-to-moderate group had a significantly lower VD in the peripapillary region on RPC network in disc areas ( p = 0.013). Conclusions Blood flow changes in macular areas might first appear at the DCP layer in OSA patients. Reduced VD in the peripapillary region at the RPC layer might be associated with OSA and cause subsequent RNFL changes.